Final shade and whiteness: impact of various ultra-thin CAD/CAM veneers and tooth-colored resin substrates - Yinghui Wang; Xia Wei; Linjuan Gao; Dingkun Liu; Xing Chen; Liujun Lin; Yu Pan; Hao Yu; Guang Hong; Hui Cheng (BMC Oral Health)
Abstract Background Achieving optimal color control in chairside CAD/CAM ultra-thin veneers, remains a significant challenge for dental clinicians and technicians. This study aims to investigate the effect of ultra-thin CAD/CAM medium translucency (MT) lithium disilicate veneers and tooth-colored resin substrates on final tooth shade and whiteness. Materials and methods Disk-shaped ceramic veneers (IPS e.max CAD MT, Ivoclar Vivadent, Liechtenstein) with a thickness of 0.3 mm were fabricated in BL2, BL3, BL4, B1, A1, A2, and A3 shades. Additionally, 4-mm thick resin substrates (Tetric N-Ceram, Ivoclar Vivadent, Liechtenstein) were prepared in A2, A3, A3.5, and A4 shades to simulate tooth-colored substrates. Veneer-resin composites were prepared by combining veneer specimens and resin substrates. Color coordinates of tooth-colored resin substrates (R), veneer-resin composites (C) and the shade guide tabs (G) were obtained using a spectroradiometer. Color differences of ΔE 00(C-R), ΔE 00(C-G) and ΔE 00(R-G) were then calculated with the CIEDE2000 formula. The initial and final shades were considered matched when ΔE 00(R-G) or ΔE 00(C-G) was clinically acceptable or minimal. Additionally, whiteness differences (ΔWI D ) between R and C specimens were recorded. Two-way analysis of variance (ANOVA) was performed, followed by the Tukey HSD. The significance level was set at p < 0.05. Results Both the shades of resin substrates and veneer shades had significant effects on ΔE 00(C-R) and ΔWI D (p < 0.001), while no interaction effects were observed (p > 0.05). They increased with darker resin substrates and lighter veneers, except for no significant differences among BL4, B1, and A1 veneers. The largest color difference was observed for BL2 veneers on A4 substrates (ΔE 00(C-R) = 6.9 ± 0.3, ΔWI D  = 19.0 ± 1.5), while the smallest occurred with A3 veneers on A2 substrates (ΔE 00(C-R) = 2.4 ± 0.6, ΔWI D  = 5.6 ± 1.0). Final tooth shades were maximally transformed to lighter shades, with A2, A3, A3.5, and A4 substrates shifting to 2M1, 2L1.5, 2R2.5, and 3L1.5, respectively. Conclusions Both resin substrates and veneer shades significantly influence final tooth shade and whiteness independently. 0.3-mm thick CAD/CAM MT lithium disilicate veneers produce substantial shade and whiteness transformations, making them effective for shade enhancement. Graphical Abstract